Sestrin2 provides cerebral protection through activation of Nrf2 signaling in microglia following subarachnoid hemorrhage - Yang, Youqing; Ding, Han; Yang, Chenxing; Wu, Jie; Bao, Youyuan; Lan, Shihai; Zhou, Lin; Zhou, Lu; Liu, Bangliang; Hong, Tao; Wan, Xichen; Wu, Xiao (Frontiers in Immunology, 2023)
Subarachnoid hemorrhage (SAH) is a neurological emergency characterized by dysfunctional inflammatory response. However, no effective therapeutic options have been reported so far. Microglia polarization has been proposed to exert an essential role in modulating inflammatory response after SAH. Sestrin2 is a stress response protein. Growing evidence has reported that sestrin2 could inhibit M1 microglia and promote M2 microglia polarization. The current study investigated the effects of sestrin2 on microglia phenotype switching and the subsequent brain injury and sought to elucidate the underlying mechanism. We conducted an endovascular perforation SAH model in mice. It was found that sestrin2 was significantly increased after SAH and was mainly distributed in neurons and microglia. Exogenous recombinant human sestrin2 (rh-sestrin2) evidently alleviated inflammatory insults and oxidative stress, and improved neurofunction after SAH. Moreover, rh-sestrin2 increased M2-like microglia polarization and suppressed the number of M1-like microglia after SAH. The protection by rh-sestrin2 was correlated with the activation of Nrf2 signaling. Nrf2 inhibition by ML385 abated the cerebroprotective effects of rh-sestrin2 against SAH and further manifested M1 microglia polarization. In conclusion, promoting microglia polarization from the M1 to M2 phenotype and inducing Nrf2 signaling might be the major mechanism by which sestrin2 protects against SAH insults. Sestrin2 might be a new molecular target for treating SAH.